2021
DOI: 10.1371/journal.pone.0258940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis ingestion on endometriosis-associated pelvic pain and related symptoms

Abstract: Background The use of cannabis for symptoms of endometriosis was investigated utilising retrospective archival data from Strainprint Technologies Ltd., a Canadian data technology company with a mobile phone application that tracks a range of data including dose, mode of administration, chemovar and their effects on various self-reported outcomes, including pelvic pain. Methods A retrospective, electronic record-based cohort study of StrainprintTM users with self-reported endometriosis was conducted. Self-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…In a 2021 retrospective cohort study of 252 endometriosis patients using cannabis, 57.3% were using it to treat their endometriosis-related pain ( 57 ). Patients reported that cannabis use was effective for their pelvic pain, gastrointestinal issues and mood ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2021 retrospective cohort study of 252 endometriosis patients using cannabis, 57.3% were using it to treat their endometriosis-related pain ( 57 ). Patients reported that cannabis use was effective for their pelvic pain, gastrointestinal issues and mood ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a 2021 retrospective cohort study of 252 endometriosis patients using cannabis, 57.3% were using it to treat their endometriosis-related pain ( 57 ). Patients reported that cannabis use was effective for their pelvic pain, gastrointestinal issues and mood ( 57 ). In a study of Australia and New Zealand-based endometriosis patients using cannabis for their pain it was reported that 72.0% and 88.2% of patients respectively, were illicitly obtaining cannabis to treat their endometriosis symptoms ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that pain relief is a major factor that EMS patients seek in their treatment, as discussed here. Based on patient surveys and preliminary studies, some cannabinoids seem to be effective in this domain, as well as showing efficacy against EM-associated gastrointestinal, sleep, and mood symptoms (Sinclair et al 2020;Sinclair et al 2021a). EMS patients using cannabis have been able to reduce dosages of other medications like non-opioid and opioid analgesics, antineuropathics, antidepressants, and antianxiety medications by at least 50% (Armour et al 2021;Sinclair et al 2021b).…”
Section: Current State Of Cannabinoid Use In Endometriosismentioning
confidence: 99%
“…Another plant, Cannabis sativa, is also addressed in pain management, due to the direct and/or indirect effects of its active principles D9-tetrahydrocannabinol (THC) and cannabidiol (CBD) on specific receptors in the endocannabinoid system. Although several different receptors are present in this system, cannabinoid receptors 1 (CB1) and 2 (CB2) present mostly in central and peripheral presynaptic neurons are the most explored, with anandamide being its main neurotransmitter [58].…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…The presence of CB1 and CB2 receptors was reported in different regions of the oocytes, according to the stage of maturation, as well as the presence of anandamide in the reproductive tract fluids. In the secretory phase, an important increase in CB1, mRNA and endometrial proteins was observed, a fact associated with the ability of progesterone to regulate the expression of these receptors [58]. In addition, a significant increase in anandamide associated with a decrease in CB1 expression has been observed in women with endometriosis, a situation that can impair the control of pain symptoms, aggravating chronic pelvic pain, dysmenorrhea and dyspareunia [58].…”
Section: Medicinal Plantsmentioning
confidence: 99%